Produção e caracterização de compósitos de CaSO4:Tb,Ag para fins dosimétricos - Silva, Anderson Manoel Bezerra da (2019)
Various materials with luminescent properties are used for ionizing radiation dosimetry by thermoluminescence (TL) and optically stimulated luminescence (OSL) techniques. In addition, several researches are being developed new TL / LOE materials and studies to improve the dosimetric properties of materials already in use. Results from the literature,some unusual rare earth elements have been shown to be promising as a dopant in CaSO4 matrix, one of which is terbium. Silver has also been used in the co-dopant function. As there are no reports on the structural characterization of CaSO4:Tb with the incorporation of silver, the purpose of this work was to produce and characterize CaSO4 crystals doped with terbium, and also with a second doping of silver oxide (Ag (OX)) and silver nanoparticles (Ag (NP)), with the purpose of using them as TL /OSL dosimeters as alternatives to those commercially available. The phosphors were produced by the slow evaporation route and characterized by X-ray diffraction (XRD), confirming the viability of the route, and by scanning electron microscopy (SEM). The silver co-dopant, which was incorporated in the form of nanoparticles, was produced by the method of Lee and Meisel and characterized by ultraviolet-visible spectrophotometry (UV-Vis), SEM and XRD.The composites in the form of tablets were obtained from the addition of Teflon to the phosphors. The TL and OSL emissions of the new materials produced were investigated. It was observed that addition of silver as a co-dopant in the CaSO4:Tb matrix alters the amount of TL emission peaks, and the presence of Ag (NP) increases the intensity of these peaks. By means of the TL emission curves of the pellets, some parameters associated to the transfer processes of the materials were determined. The lower limit of detection and the TL emission spectrum of the composites were also evaluated.The phosphors presented a typical exponential OSL decay curve , with change from fast component to very slow component due to the incorporation of silver in the CaSO4:Tb matrix, which indicates that the charge capture centers are not highly optically active for LEDs blue. The crystals of CaSO4:Tb,Ag (NP) presented higher sensitivity than CaSO4:Tb,Ag (Ox). All samples have a luminescente signal reproducible and linear , with TL /OSL responses proportional to the absorbed dose.